What is the impact of titanium particles and biocorrosion on implant survival and complications? A critical review. (10th October 2018) - Mombelli, Andrea; Hashim, Dena; Cionca, Norbert
Abstract: Objectives: To compile the current evidence regarding the association between the release of titanium particles and biologic complications of dental implants. Material and methods: This is a critical review. We searched the literature using the terms "corrosion, " "allergy, " "hypersensitivity, " or "particles" together with "titanium, " "Ti, " "TiO2. " The bibliographies of identified publications and previously published review articles were scanned to find additional related articles. We included clinical studies, in vivo and in vitro experiments. Results: Titanium particles and degradation products of titanium have been detected in oral and nonoral tissues. Particles are released from surfaces of dental implants because of material degradation in a process called tribocorrosion. It involves mechanical wear and environmental factors, notably contact to chemical agents and interaction with substances produced by adherent biofilm and inflammatory cells. In vitro, titanium particles can interfere with cell function and promote inflammation. A temporal association between exposure to titanium and occurrence of tissue reactions suggested hypersensitivity in a limited number of cases. However, there is poor specificity as the observed reactions could be initiated by other factors associated with the placement of implants. Titanium particles are commonly detected in healthy and diseased peri‐implant mucosa alike, at low levels even in gingiva of individuals without titanium implants. Rather than being the trigger of disease, higher concentrations of titanium in peri‐implantitis lesions could be the consequence of the presence of biofilms and inflammation. Conclusion: There is an association between biocorrosion, presence of titanium particles, and biological implant complications, but there is insufficient evidence to prove a unidirectional causal relationship.